EKSISTENSI BAHASA MELAYU DI KOTA PEKANBARU - Satrio Rachmazan; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aims to understand the condition of the existence of the malay language in pekanbaru .Where factor-faktor that affect the existence of the malay language it is still less public awareness riau will to maintain the malay language in pekanbaru This research using 5 the informant consisting of figures customary , the youth , the scholars , municipal pekanbaru and customs institutions pekanbaru riau city . An analysis of this research wears the manner triangulation with theory is clear that these cannot on a check with degrees trust with one or more theory . For it , should step in do is seek explanation appeal or komparasi with unravel relationship pattern and menyertakanpenjelasan that emerged from the analysis to find the theme of the possibility for comparison based on data available .Then the data has been collected is to be served in a descriptif in the form of qualitative . So the result of research is ) 1.That is still very low pekanbaru own people who uses malay.2 ) factors awareness and cultural socialization ( language of ) malay stakeholders like family, customs institutions malays riau city pekanbaru and municipal pekanbaru a weak and impressed ignored.3 ) there will be the joint effort from stakeholders this to be together to resolve the culture ( language ) malays in the city pekanbaru.Keywords: Existence and the malay language